Nanosensor for carcinoembryonic antigen (CEA) detection based on a selective growth-regulating mechanism - Johan A. Farfán; Mary Licuona; Betty C. Galarreta; Yulán Hernández (Sensors International, 2025)
Nanomaterial-based biosensors provide high sensitivity and versatility for the detection of target analytes. Particularly, gold nanomaterials are widely employed as signal transducers due to their unique plasmonic properties. When functionalized with aptamers, these nanostructures gain enhanced selectivity, rapid response capability, and cost-effectiveness. However, the instability of large gold nanoparticles can hinder the exploration of various shapes and sizes.In this research, two different types of nanoparticles were used for the development of a carcinoembryonic antigen (CEA), a tumoral biomarker for colorectal cancer, nanosensor. It was proposed a system based on gold nanotriangles (AuNTs) functionalized with the amphiphilic polymer polyvinylpyrrolidone (AuNT@PVP) and a hairpin-shaped aptamer selective to CEA biotinylated at the 3′ end and thiolated at the 5′ end (AuNT@PVP@Apt). Specific recognition process was optimized expecting that CEA would trigger the unfolding of the hairpin structure, exposing biotin moieties that enabled subsequent binding of streptavidin-functionalized gold nanoparticles (AuNP@Strept, 3–5 nm in diameter). However, when analyzing the optical changes observed by UV–Vis–NIR spectroscopy and its correlation with the concentration of CEA, it was observed that the main mechanism involved in the detection was a selective growth mechanism of AuNPs, leading to a really simple and easy way of detecting CEA. The results obtained in this study highlight the intricacies of developing such nanosensors and introduce a novel detection method based on a selective growth mechanism that can be further used for detection.